Sustained remission after haploidentical bone marrow transplantation in a child with refractory systemic juvenile idiopathic arthritis - Guillaume Morelle (Pediatric Rheumatology Online Journal, 2021)
Abstract Background Some patients with systemic juvenile idiopathic arthritis (SJIA) and severe, refractory disease achieved remission through intensive immunosuppressive treatment followed by autologous hematopoietic stem cell transplantation (HSCT). However, disease relapsed in most cases. More recently selected SJIA patients received allogenic HSCT from a HLA-identical sibling or a HLA matched unrelated donor. While most transplanted patients achieved sustained SJIA remission off-treatment, the procedure-related morbidity was high. Case report A girl presented SJIA with a severe disease course since the age of 15 months. She was refractory to the combination of methotrexate and steroids to anti-interleukin (IL)-1, then anti-IL-6, tumor necrosis factor alpha inhibitors, and thalidomide. Given the high disease burden and important treatment-related toxicity the indication for a haploidentical HSCT from her mother was validated, as no HLA matched donor was available. The patient received a T replete bone marrow graft at the age of 3.7 years. Conditioning regimen contained Rituximab, Alemtuzumab, Busulfan, and Fludarabine. Cyclophosphamide at D + 3 and + 4 post HSCT was used for graft-versus-host-disease prophylaxis, followed by Cyclosporin A and Mycophenolate Mofetil. Post HSCT complications included severe infections, grade 3 intestinal graft-versus-host-disease, autoimmune thyroiditis, and immune thrombocytopenia. Three years after HSCT, the child is alive and well, notwithstanding persistent hypothyroidy requiring substitution. Immune thrombocytopenia had resolved. Most importantly, SJIA was in complete remission, off immunosuppressive drugs. Conclusion Allogenic HSCT may be a therapeutic option, even with a HLA haplo-identical alternative donor, in patients with inflammatory diseases such as SJIA. Despite increased experience with this treatment, the risk of life-threatening complications restrains its indication to selected patients with severe, refractory disease.